Kritičen pogled na prosto dostopne zdravstvene informacije na spletu - Klemenčič, Eva (Informatica Medica Slovenica, 2006)
Easy accessible Internet with its vast amount of information is more and more often used for searching health information, which should be contemporary and authorised. As an example we will show time distribution of records in MEDLINE, in Slovenian bibliographic database Biomedicina Slovenica and in Google. Then we will show some factors that have important impact on choosing suitable and relevant information. While searching health information we shouldn't ignore the free access services like Wikipedia or Google. They can be used for fast finding of information candidates from which the selected should be verified in authorised and competent free access databases like MedlinePlus.
Keywords: Computer Communication Networks; Databases, Bibliographic; Evaluation Studies; Health Education; Medline; Ocenjevalne študije; Računalniške mreže; Zbirke podatkov bibliografske; Zdravstvena vzgoja